THEORY AND METHODOLOGY OF TEACHING IN ART BOOK IN BULGARIA. DEPICTIVE, SPATIAL AND CONSTRUCTIVE APPROACH IN REGINA DALKALACHEVA’S ART AS A CONTRIBUTION TO UNDERSTANDING ART BOOK AS A SUBJECT - Kapka Kaneva (Издател)
The publication follows the stages of development of the “Art Book” academic discipline as a key to the teaching methodology in “Book, Illustration, Printed Graphics” Department of the National Academy of Art. A parallel is drawn between the personal artistic achievement of Regina Dalkalacheva and the evolution of understanding art book at an academic level – both as a creative direction in the field of independent book publications, and as philosophy, as a social and cultural phenomenon. Through comparative and morphological analysis of Dalkalacheva’s iconic works the process of constituting the art book genre as a specific and highly creative artistic act, both to herself and to the Bulgarian book art, is illustrated